Representing the past in the art of the long nineteenth century
1 online resource
Keywords: "This edited collection explores the intersection of historical studies and the artistic representation of the past in the long nineteenth century. The case studies provide not just an account of the pursuit of history in art within Western Europe but also examples from beyond that sphere, including canonical and conventional examples of history painting as well as more inclusive, 'popular' and vernacular visual cultural phenomena. General themes explored include the problematics internal to the theory and practice of academic history painting and historical genre painting, including compositional devices and the authenticity of artefacts depicted; relationships of power and purpose in historical art; the use of historical art for alternative Liberal and authoritarian ideals; international cross-fertilisation of ideas about historical art; and exploration of the diverse influences of socioeconomic and geopolitical factors. This book will be of particular interest to scholars of the histories of nineteenth-century art and culture"--